Relasi Kuasa pada Kasus Pelecehan Seksual dalam Film Dear Nathan: Thank You Salma - Davina Puspa Ningrum; Siti Rohana Hariana Intiana; Marlinda Ramdhani (Mataram University, 2026)
This research is motivated by the emergence of films in Indonesia that depict power relations in cases of sexual harassment, particularly in one of the well-known films in Indonesia, Dear Nathan: Thank You Salma, which focuses on the power of the sexual harasser who holds a high social position to pressure the victim. This study aims to describe the forms of power relations, identify the oppression experienced by the victim, and analyze the psychological impacts arising from sexual harassment in the film Dear Nathan: Thank You Salma. This research employs a qualitative approach. The research data consist of dialogues and scene excerpts from the film Dear Nathan: Thank You Salma. Data collection methods include the listening method with observation, note-taking, and documentation techniques. Using liberal feminist theory, this study highlights the importance of protecting women's rights and providing social support in addressing injustice within educational settings. The findings reveal twenty data points related to power relations, forms of oppression, and psychological impacts. Specifically, ten data points concern power relations, seven data points concern forms of oppression, and three data points concern psychological impacts.